The Effect Of Facebook Followers' Interaction On The Expected Quality Of Food Commodities (a Case Study Of Enjoy Plus Company In Zarqa City/jordan) - Mustafa Akaileh; Khaled Tawfeq Al Assaf; Mustafa S. Al-shaikh; Sir Marwan A. Lafee (جامعة الوادي University of Eloued, 2024)
Nowadays, Facebook Followers in marketing perspective are extremely Seek to reach and access to most brands all over the world. Facebook followers are considered a double-edged, grant brands an advantage to achieve their targets. As they impact consumers’ intentions to buy. The main purpose of this study is to investigate the influence of Facebook followers' interaction on expected food quality, using Enjoy Plus company in Jordan as a case study. The study used four influence factors, (Comments, participating, like, tag, and followup) as independent variables (IV), while the dependent variable (DV) is expected quality. Quantitative survey data was collected from 396 followers. Regression analysis revealed a significant positive effect of social media interaction on expected quality. Specifically, comments and responses had the strongest influence, explaining 77.3% of variance. The findings provide practical implications for food companies in utilizing Facebook tools to shape followers' service quality perceptions. Further research across industries and cultural contexts is warranted to expand on the conclusions
Keywords: Expected Quality; Enjoy Plus Company; Food Products; Interaction with followers on Facebook; Jordan